Patient satisfaction with humanistic nursing in Chinese secondary and tertiary public hospitals: a cross-sectional survey - Liu, Yilan; Zhang, Fengjian; Guan, Chunyan; Song, Bing; Zhang, Haixin; Fu, Mo; Wang, Fang; Tang, Chenxi; Chen, Huiling; Guo, Qingfeng; Fan, Ling; Hou, Xinfeng; et al. (Frontiers in Public Health, 2023)
Background Humanistic care pertains to the abilities, attitudes, and behaviors central to patient-centered care, contributing to patients' sense of safety and wellbeing. This study aimed to assess the satisfaction of patients with humanistic nursing care in Chinese secondary and tertiary public hospitals. Methods A national cross-sectional survey was conducted across 30 provinces and 83 hospitals in China. Patient satisfaction with humanistic care was assessed using the Methodist Health Care System Nurse Caring Instrument (NCI), which encompasses 20 items across 12 dimensions. Each item was rated on a 7-point Likert scale, yielding a total score of 140. Multiple linear regression analysis was employed to identify factors associated with patients' satisfaction. Results Moderate satisfaction (mean score 91.26 ± 13.14) with humanistic nursing care was observed among the 17,593 participants. Factors significantly associated with patient satisfaction included age, hospital type, presence of children, educational attainment, place of residence, family monthly income, and medical insurance type. Conclusion The study findings highlight the importance of tailored interventions, evidence-based practice guidelines, and patient-centered care in improving patients' satisfaction with humanistic nursing care. Continuous emphasis on nursing education and professional development is crucial for enhancing humanistic care and patient satisfaction.